Passengers departing on the Wild Goose Railroad for July 4th picnic, vicinity of Nome, Alaska, 1901. - Hegg, Eric A., 1867-1948 (1901)
Passengers departing on the Wild Goose Railroad for July 4th picnic, vicinity of Nome, Alaska, 1901.